1993
DOI: 10.1016/0014-5793(93)81627-c
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mammalian cell proliferation by a modified tRNA base of bacterial origin

Abstract: Addition of the q-base to q-deficient non-transformed mammalian cells stimulated their proliferation. The q-base also improved proliferation of some cancer-derived cell lines, but inhibited proliferation of others. The proliferation of HeLa-S3 carcinoma cells was stimulated by q under aerobic conditions, but was inhibited when the cells had shifted their energy metabolism towards glycolysis as the result of oxygen limitation. Q-deficient cells could not adapt their proliferation to the respective oxygen tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…q stimulates the proliferation of non-transformed NIH-3T3 cells, but inhibits the proliferation of rus-transformed NIH-3T3 cells. Transformation of NIH-3T3 cells with the rus oncogene causes a shift of the metabolism from respiration towards glycolysis even under aerobic conditions as indicated by an increase in lactate production [22]. Cell proliferation, glucose metabolism and the stress response are processes that are controlled by receptors for growth factors or hormones [53-551.…”
Section: Discussionmentioning
confidence: 99%
“…q stimulates the proliferation of non-transformed NIH-3T3 cells, but inhibits the proliferation of rus-transformed NIH-3T3 cells. Transformation of NIH-3T3 cells with the rus oncogene causes a shift of the metabolism from respiration towards glycolysis even under aerobic conditions as indicated by an increase in lactate production [22]. Cell proliferation, glucose metabolism and the stress response are processes that are controlled by receptors for growth factors or hormones [53-551.…”
Section: Discussionmentioning
confidence: 99%
“…Since Q is a nutrient factor for eucaryotes, they contain Q as the free base as well, whereas eubacterial cells do not contain the free Q base. In eucaryotes, Q might be involved in many cellular processes such as differentiation (10,32), the management of hypoxic stress (25,26), the regulation of protein synthesis (25), the adaptive regulation of cell proliferation to the metabolic predisposition (18), and the modulation of signal transduction pathways (17).…”
Section: The Hypermodified Trna Nucleoside Queuosine [Q: 7-(((45-cismentioning
confidence: 99%
“…In contrast to eubacteria, eukaryotes cannot synthesize queuine de novo and are required to obtain queuine from diet or gut flora as a nutrient factor (Reyniers et al 1981). Although its physiological role is largely unclear, queuine modification of tRNA has been suggested to be involved in cell differentiation, proliferation, and response to oxidative stress (Langgut et al 1993;Reisser et al 1994;Pathak et al 2007). In addition, it was reported that queuine-and tyrosine-deficient mice showed severe abnormalities such as labored breathing, seizures, and even death in some cases (Marks and Farkas 1997).…”
Section: Introductionmentioning
confidence: 99%